Effect of multicomponent interventions on tuberculosis notification in mining and pastoralist districts of Oromia region in Ethiopia: a longitudinal quasi-experimental study - Degu Jerene; Daniel Gemechu Datiko; Liza Marlette de Groot; Zewdu Gashu Dememew; Nebiyu Hiruy; Solomon Negash Gebreyes; Pedro G Suarez (BMJ Open, 2023)
Objective To demonstrate the impact of interventions on tuberculosis (TB) case detection in mining and pastoralist districts in southeastern Ethiopia over a 10-year period.Design Longitudinal quasi-experimental study.Setting Health centres and hospitals in six mining districts implemented interventions and seven nearby districts functioned as controls.Participants Data from the national District Health Information System (DHIS-2) were used for this study; therefore, people did not participate in this study.Interventions Directed at training, active case finding and improving treatment outcomes.Primary and secondary outcome measures Primarily, trends in TB case notification and percentage of bacteriologically confirmed TB—as collected by DHIS-2—between pre-intervention (2012–2015) and post-intervention (2016–2021) were analysed. Secondarily, post-intervention was split into early post-intervention (2016–2018) and late post-intervention (2019–2021) to also study the long-term effects of the intervention.Results For all forms of TB, case notification significantly increased between pre-intervention and early post-intervention (incidence rate ratio (IRR): 1.21, 95% CI: 1.13, 1.31; p<0.001) and significantly decreased between pre-intervention/early post-intervention and late post-intervention (IRR: 0.82, 95% CI: 0.76, 0.89; p<0.001 and IRR: 0.67, 95% CI: 0.62, 0.73; p<0.001). For bacteriologically confirmed cases, we found a significant decrease between pre-intervention/early post-intervention and late post-intervention (IRR: 0.88, 95% CI: 0.81, 0.97; p<0.001 and IRR: 0.81, 95% CI: 0.74, 0.89; p<0.001). The percentage of bacteriologically confirmed cases was significantly lower in the intervention districts during pre-intervention (B: −14.24 percentage points, 95% CI: –19.27, –9.21) and early post-intervention (B: −7.78, 95% CI: –15.46, –0.010; p=0.047). From early post-intervention to late post-intervention, we found a significant increase (B: 9.12, 95% CI: 0.92 to 17.33; p=0.032).Conclusions The decrease in TB notifications in intervention districts during late post-intervention is possibly due to a decline in actual TB burden as a result of the interventions. The unabated increase in case notification in control districts may be due to continued TB transmission in the community.